Gliadin antibodies in older population and neurological and psychiatric disorders. (12th April 2012) - Ruuskanen, A.; Kaukinen, K.; Collin, P.; Krekelä, I.; Patrikainen, H.; Tillonen, J.; Nyrke, T.; Laurila, K.; Haimila, K.; Partanen, J.; Valve, R.; Mäki, M.; et al.
<x xml:space="preserve">Abstract</x> Objectives A variety of neurological and psychiatric disorders have recently been linked to coeliac disease and gluten sensitivity. We here explored whether persistently positive gliadin antibodies (AGA) and coeliac‐type HLA increase the risk of gluten sensitivity‐related neurological and psychiatric manifestations. The study was carried out in an older population who had consumed gluten for decades but who had no previous coeliac disease diagnosis. Materials and Methods The original study population comprised 4272 randomly selected older individuals, of whom 2089 had AGA and transglutaminase 2 antibodies (antiTG2) measured twice within a 3‐year interval. Forty‐nine persistently AGA‐positive but antiTG2‐negative subjects with coeliac‐type HLA and 52 randomly selected persistently AGA‐ and antiTG2‐negative age‐ and sex‐matched controls were clinically examined for neurological disorders. The Psychological General Well‐Being (PGWB) questionnaire, the SF‐36 health survey questionnaire and the Depression Scale (DEPS) were employed to evaluate psychological well‐being. The medical files of all the study subjects were analysed for previous illnesses. Results Persistently AGA‐positive but antiTG2‐negative older subjects carrying coeliac disease‐type HLA did not evince significantly more neurological symptoms or diseases than AGA‐negative control subjects (P = 0.682, P = 0.233). There were no statistically significant differences between AGA‐positive and AGA‐negative groups in psychological well‐being and quality of life when measured by PGWB (P = 0.426), SF‐36 questionnaires (P = 0.120) and DEPS (P = 0.683). Conclusions At population level, persistent AGA positivity did not indicate gluten sensitivity‐related neurological and psychiatric disorders.